Four Additional Doses of PEG-L-Asparaginase During the Consolidation Phase in the AIEOP-BFM ALL 2009 Protocol Do Not Improve Outcome and Increase Toxicity in High-Risk ALL: Results of a Randomized Study - Conter, Valentino; Valsecchi, Maria Grazia; Cario, Gunnar; Zimmermann, Martin; Attarbaschi, Andishe; Stary, Jan; Niggli, Felix; Dalla Pozza, Luciano; Elitzur, Sarah; Silvestri, Daniela; Locatelli, Franco; Möricke, Anja; et al. (Journal of clinical oncology, 2024)
PURPOSE: The AIEOP-BFM ALL 2009 protocol included, at the end of the induction phase, a randomized study of patients with high-risk (HR) ALL to investigate if an intensive exposure to pegylated L-asparaginase (PEG-ASNASE, 2,500 IU/sqm once a week × 4) on top of BFM consolidation phase IB allowed us to decrease minimal residual disease (MRD) and improve outcome. PATIENTS AND METHODS: A total of 1,097 patients presented, from June 2010 to February 2017, with one or more of the following HR criteria: KMT2A::AFF1 rearrangement, hypodiploidy, prednisone poor response, poor bone marrow response at day 15 (Flow MRD ≥10%), or no complete remission (CR) at the end of induction. Of them, 809 (85.1%) were randomly assigned to receive (404) or not receive (405) four weekly doses of PEG-ASNASE. RESULTS: By intention to treat (ITT) analysis, there was no significant difference in the proportion of patients with polimerase chain reaction MRD ≥5 × 10-4 at the end of phase IB in the experimental versus control arm (13.9% v 17.0%, P = .25). The 5-year event-free survival (median follow-up 6.3 years) by ITT in the experimental and control arms was 70.4% (2.3) versus 75.0% (2.2; P = .18), and the 5-year overall survival was 81.5% (2.0) versus 84.0% (1.9; P = .25), respectively. The corresponding 5-year cumulative incidence of death in CR was 9.5% (1.5) versus 5.7% (1.2; P = .08), and that of relapse was 17.7% (1.9) versus 17.2% (1.9), respectively (P = .94). Adverse reactions in phase IB occurred in 22.2% and 8.9% of patients in the experimental and control arm, respectively (P < .001). CONCLUSION: Additional PEG-ASNASE in phase IB did not translate into a benefit for decreasing relapse incidence but was associated with higher toxicity. Further improvements with conventional chemotherapy might be difficult in the context of intensive treatment protocols.
Keywords: recidiva; Disease-Free Survival; Infant; Treatment Outcome; lokální recidiva nádoru; Recurrence; protokoly protinádorové kombinované chemoterapie; polyethylenglykoly; Asparaginase; Humans; randomizované kontrolované studie jako téma; asparaginasa; Antineoplastic Combined Chemotherapy Protocols; Randomized Controlled Trials as Topic; Polyethylene Glycols; přežití bez známek nemoci; kojenec; prednison; Prednisone; akutní lymfatická leukemie; Neoplasm Recurrence, Local; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé; výsledek terapie